Balancing Act: Examining the Efficacy of Environmental Protection Laws in Natural Resource Management - Fauzan Saputro (Proceeding International Conference Restructuring and Transforming Law, 2024)
This abstract explores the intricate interplay between environmental protection laws and their effectiveness in the realm of natural resource management. Termed a "Balancing Act," the study scrutinizes the delicate equilibrium between regulatory frameworks and the practical conservation of natural resources. The investigation delves into the multifaceted nature of environmental protection laws, evaluating their design, implementation, and impact on sustainable resource utilization. By examining case studies and legal precedents, the research aims to elucidate the successes and challenges associated with these laws. It also considers the dynamic environmental landscape, acknowledging the need for adaptive legal mechanisms to address emerging issues. The efficacy of environmental protection laws in promoting conservation and mitigating environmental degradation is analyzed through a comprehensive lens. The study scrutinizes the enforcement mechanisms, regulatory compliance, and the role of stakeholders in achieving the intended conservation outcomes. Potential gaps and shortcomings in the existing legal frameworks are identified, and recommendations for improvement are proposed. In conclusion, "Balancing Act" contributes valuable insights into the ongoing discourse on environmental protection laws and their impact on natural resource management. By unraveling the complexities of this intricate relationship, the research seeks to inform policymakers, legal practitioners, and environmental advocates on optimizing regulatory frameworks for a sustainable and harmonious coexistence between human activities and the natural environment.